DEPRECIATION POLICY: REPAIRS AND REPLACEMENTS. - Devine, Carl (The Accounting Review, 1941)
Abstract The article focuses on repairs and replacements concerning depreciation policy. Accountants writing in the field of depreciation, particularly with regard to repairs, renewals, replacements, betterments, etc., have placed what seems to the author undue emphasis on the physical and productive aspects of the problem. Such criteria for accounting procedures do not offer a rational basis for the solution of many accounting difficulties which arise in this field. There are cases, no doubt, in which the replacing of a simple rivet or bolt will increase the productivity of a complicated machine from zero to one hundred per cent. Moreover, the fact that an "extraordinary" repair will probably increase the service life of the entire machine or make the unit perform more efficiently, while of critical importance in guiding the management in reaching the decision to make the change, ordinarily does not constitute a rational basis for determining whether the expenditure should be taken to operations in the period of incurrment or deferred to future operations.